Consensus workshop on methods to evaluate developmental immunotoxicity. - Luster, Michael I (2003)
A workshop cosponsored by the National Institute of Environmental Health Sciences and the National Institute for Occupational Safety and Health was convened in Washington, DC, on 17-18 October 2001 with the goal of developing a consensus document on the most appropriate experimental approaches and assays available to assess developmental immunotoxicity. The work group was composed of scientists from academia, the chemical and pharmaceutical industries, and federal agencies with expertise in developmental immunology, developmental toxicology, immunotoxicology, and risk evaluation. This consensus document presents an overview of the major summations made by the work group. A summary of early work in the field is provided, which includes potential immunotoxic agents, followed by brief discussions of our current understanding of developmental immunology. This report concludes with the work group's consensus of the most appropriate experimental design and tests to screen for potential developmental immunotoxic agents in experimental models, including potential limitations and data gaps.